DETERMINATION OF RESIDUAL VOLTAGES IN A FOLDED CROSS-SECTION OF A FLAT BAR WITH A CURVULAR LONGITUDINAL AXIS - Буланов, В. В.; Полтарушников, А. С. (Proceedings of National Aviation University (archive), 2021)
The method of determining the residual stresses in the curved beam of the composite cross section is considered.